IRRITATION TEST OF LIQUID ANTIBACTERIAL SOAP COMBINING LEGUNDI AND GREEN BETEL LEAVE EXTRACTS ON WHITE RATS (Rattus norvegicus) - Suyasa, Ida Bagus Oka; Dewi, Ni Nyoman Astika; Apriliapatni, Made Delia Budi; Bryan, Surya Natallia (Meditory : The Journal of Medical Laboratory, 2025)
Background: Soap is a cleanser that is made with a chemical reaction. Soap preparations with active ingredients derived from nature are also widely circulated. Natural ingredients that have many active substances are legundi leaves and green betel leaves. Two antimicrobial agents from these ingredients working simultaneously on a homogeneous microbial population will have a synergistic effect.Objective: This study aims to determine the safety of using an antibacterial liquid soap formula with a combination of legundi and betel leaf extracts.Methods: This study is an experimental research that includes physicochemical testing of the soap formula, organoleptic evaluation, and irritation testing on white rats (Rattus norvegicus) using the Draize method with a posttest-only control group design. This research was analyzed descriptively. This study adheres to the ethical principle of beneficence, prioritizing the well-being and safety of all participants.Results:  Organoleptic test, pH test, homogeneity test, and water content test meet Indonesian National Standard requirements, and there is no irritation in experimental animals.Conclusions: An antibacterial liquid soap formula with a combination of legundi and betel leaf extracts is safe.